A multi-scale methods comparison to provide granitoid rocks thermal conductivity. (18th October 2021) - Coletti, Chiara; Borghi, Alessandro; Cossio, Roberto; Chiara Dalconi, Maria; Dalla Santa, Giorgia; Peruzzo, Luca; Sassi, Raffaele; Vettorello, Arianna; Galgaro, Antonio
Highlights: Thermal conductivity of granitoids is mainly controlled by mineralogical content. Size and texture of minerals are fundamental in the grain-to-grain heat transfer. Thermal modelling represents a valuable tool in a priori thermal characterization. Abstract: Granitoid rocks are frequently used in modern construction and restoration, hence the importance of knowing their petrophysical properties. These rocks find several applications in various types of surfaces, from flooring to walls, coupled to radiant devices for indoor air conditioning or as geological target in hot dry rock geothermal systems. In order to support the thermophysical characterization, the thermal conductivity of seven granitoid rocks belonging to five different lithologies (granodiorite, tonalite, granite, gabbro, and syenite) has been analysed, as main property which must to be assessed, by comparison between traditional measurement methods and a new analytical approach. In detail, the thermal conductivity was measured directly on the bulk rock samples, evaluated by applying Quantitative Phase Analysis starting from the Digital Imaging Analysis (DIA) and Rietveld refinement associating thermal parameters to each phase, and analysed by thermal modelling. Thermal simulation obtained by the 2D modelling highlights on the dependence of the thermo-physical properties of considered rocks from the minerals content, according to the abundance of quartz, as well as to the mineral's grain size and the geometrical grain distribution. This procedure provides a reliable estimation of the rock's thermal behaviour considering concurrently different mineralogical and textural parameters. The comparison between different approaches to thermal conductivity evaluation of granitoids allowed to consider the validity of the predictive approach, based on thermal modelling. The methodologies here developed and compared considering the thermal properties of granitic rocks can be extended and optimized for other types of rocks.